The association of lipid-lowering therapy and blood pressure control among outpatients with hypertension at the Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia - Abebe, Rahel Belete; Kebede, Sewnet Adem; Birarra, Mequanent Kassa (Frontiers in Cardiovascular Medicine, 2023)
Background The lipid-lowering medications known as statins have been shown in controlled clinical trials to have pleiotropic properties, such as lowering blood pressure, in addition to lowering cholesterol levels. The purpose of this study was to see if there was a possible link between blood pressure control and statin therapy in outpatients with hypertension in a real clinical setting. Patients and methods A retrospective comparative cohort study of 404 patients with hypertension was carried out. A systematic random sampling technique was used. For data entry, Epi-Data version 4.6 was used, and SPSS version 25 was used for further analysis. For group comparisons, chi-square and independent t-tests were computed. To determine the relationship between statin use and blood pressure control, a binary logistic regression model was employed. To declare statistical significance, a 95% confidence interval and a P-value of <0.05 were used. Results Half of the study participants who were using a prescribed statin were assigned to the statin group, whereas the remaining participants who do not take statins were assigned to the control group. After 3 months of statin treatment, BP control to <130/80 mmHg was significantly greater (P = 0.022) in the statin group (52.5%) than in the control group (41.0%). The use of statins raises the likelihood of having blood pressure under control by 1.58 times when compared to statin non-users. After controlling for possible confounders, statin therapy still increased the odds of having controlled BP by a factor of 5.98 [OR = 5.98; 95% CI: 2.77–12.92]. Conclusion This study revealed that blood pressure control was higher among statin user hypertensive patients. Favorable effects of statin use were independently observed, even after correction for age, presence of dyslipidemia, and duration of antihypertensive therapy. Therefore, the importance of concomitantly added lipid-lowering drugs such as statins and their role in managing poor blood pressure control should be given due emphasis.